Analisis Framming Pemberitaan Ibu Kota Negara (IKN) Pada Media Nasional CNN Indonesia Dan Kompas.Com - Yogi Witanto; Sumaina Duku; Ahmad Harun Yahya (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
The relocation of the National Capital (IKN) from Jakarta to East Kalimantan has become a national strategic issue that has caused public debate. The online media CNN Indonesia is quite routine in reporting the relocation of the new national capital from various aspects, including economics, legislation, and socio-culture. Framing analysis is one of the journalistic communication strategies that aims to create the image, ideas, and style desired and expected by the media and companies. This study aims to determine the news framing in the issue of the Relocation of the National Capital in the online media CNN Indonesia. This study uses a qualitative descriptive research type. Data collection techniques are carried out using survey techniques and document analysis techniques. The data analysis technique in this study uses the Zhongdang Pan and Kosicki Framing analysis technique, which has four structures, namely, syntax, script, thematic, and rhetorical. The results of this study indicate that there are significant differences in the news framing approach between the two media. CNN Indonesia often emphasizes a critical perspective and in-depth analysis of policy issues and social impacts, creating a more skeptical narrative of government projects, including the National Capital (IKN). They focus on the implications and controversies surrounding the development. Meanwhile, Kompas.com tends to be more informative and narrative, focusing on delivering factual information, history, and the meaning of the name of the new Capital City, providing a broader context. They avoid direct criticism, highlighting the reasons behind government decisions. This research is expected to be an evaluation and suggestion for CNN Indonesia and Kompas.com, that the principle of neutrality and objectivity is very crucial in news reporting. In addition, for the community who utilize the media, it is expected to further increase intelligence in understanding the news.